2022
DOI: 10.1108/itp-02-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' purchase intentions in social commerce: the role of social psychological distance, perceived value, and perceived cognitive effort

Abstract: PurposeElectronic word-of-mouth (eWOM) has become one of the most influential information sources for consumers' purchase decision-making. Based on construal-level theory and from the perspective of cognitive effort, this study investigated the effects of eWOM social media types and conflicting eWOM on consumers' purchase intentions and validated the mediation role of social psychological distance, perceived value, and perceived cognitive effort.Design/methodology/approachTwo scenario-based experiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 87 publications
1
14
0
2
Order By: Relevance
“…What is more, it is observed that psychological distance positively influences the green perceived value. This finding follows the results of a previous study [27], with the difference that it focused on the effect of the perceived value derived from word-of-mouth in response to networks. The data from the study showed that psychological distance was the variable with the highest degree of influence on green perceived value among all variables.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…What is more, it is observed that psychological distance positively influences the green perceived value. This finding follows the results of a previous study [27], with the difference that it focused on the effect of the perceived value derived from word-of-mouth in response to networks. The data from the study showed that psychological distance was the variable with the highest degree of influence on green perceived value among all variables.…”
Section: Discussionsupporting
confidence: 90%
“…It also involves an individual’s subjective judgment of their acceptance [ 26 ]. In the marketing sector, it is widely acknowledged that consumers’ perception of psychological distance can significantly impact their cognitive and decision-making processes [ 27 , 28 , 29 ]. Therefore, psychological distance, like social identity, significantly impacts consumers from the perspective of influencing cognition, whereas green perceived value affects consumers from a comprehensive evaluation standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Third, this study contributes to the research on WOM by demonstrating that individuals' response behaviors toward help-requests embedded in HMCs can take the form of proactive helping, reactive helping, or inaction. Most of the existing WOM studies focus on increasing individuals' response rates (Fatkin and Lansdown, 2017) and consider individuals' responses to marketing campaigns as a binary concept, such as purchase (Yang, 2022) and sharing (Wang et al ., 2021). Based on the dichotomy of reactive and proactive behaviors (Spitzmuller and Van Dyne, 2013), this study depicts recipients' responses to HMCs as proactive helping, reactive helping and inaction.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was performed in Credamo, a questionnaire publishing website accessible via mobile or PC Internet devices. Credamo has been widely used and can provide attentive subjects and valid data (Chen & Yan, 2023; Li et al, 2023; Su & Li, 2023; Wang et al, 2022; Yang, 2022). We employed purposive sampling, a non‐probabilistic technique, to select participants who were registered with Credamo and had prior experience using AI virtual assistants.…”
Section: Methodsmentioning
confidence: 99%